2018
DOI: 10.1097/md.0000000000011692
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio, obesity, and breast cancer risk in Chinese population

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
0
18
1
Order By: Relevance
“…However, only three prior studies, all conducted in Asian women, assessed the association between NLR and risk of breast cancer 7,17,18 . Two of the three studies compared breast cancer cases with patients with benign breast disease (BBD) 7,17 , and only one used healthy controls as comparison group 18 , as in our study. In one of the studies 17 , NLR was significantly higher in the breast cancer group compared with the BBD group, and patients with NLR > 1.67 were associated with an increased risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only three prior studies, all conducted in Asian women, assessed the association between NLR and risk of breast cancer 7,17,18 . Two of the three studies compared breast cancer cases with patients with benign breast disease (BBD) 7,17 , and only one used healthy controls as comparison group 18 , as in our study. In one of the studies 17 , NLR was significantly higher in the breast cancer group compared with the BBD group, and patients with NLR > 1.67 were associated with an increased risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that a different mechanistic pathway may exist between breast cancer patients and healthy controls by menopausal status, however, we found no evidence in the literature in support of this. A previous study conducted in Chinese women using BBD as controls examined the NLR-BC association by menopausal status and found that intermediate and high NLR levels significantly increased breast cancer risk compared to very low NLR levels in both, pre-and postmenopausal women 17 . In another study of ovarian cancer cases, total neutrophil counts and WBC were significantly increased in premenopausal women who were Jewish 35 , and premenopausal women who had a family history of breast or ovarian cancer also had higher NLR and lower lymphocyte counts 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher NLR in healthy smokers compared to nonsmokers is in agreement with previous results (Tulgar et al, 2016, Gumus et al, 2018). An elevated NLR has been associated with increased risk for breast cancer (Fang et al, 2018), whereas this is not documented in HNC and needs further studies.…”
Section: Smoking Effect On Biomarkersmentioning
confidence: 92%
“…Overall, the risk for BC was increased by 49% in adult females with MetS and considered statistically significant and with moderate heterogeneity (RR = 1.49, 95% CI = 1.31-1.70, p < 0.0001, I 2 = 78.8%, random effect model). When 1 study was excluded, I 2 would decrease to 70.5%, with a slight increase in RR (1.56) [22]. Besides, due to using different methods to calculate RR, we divided the studies into cohort and case-control studies.…”
Section: Meta-analysis Of Whole Studiesmentioning
confidence: 99%